Study of WMAN Physical Layer under Fading Channels - Fahad Frayyeh, Hatem (Anbar Journal of Engineering Sciences, 2016)
WMAN (wireless metropolitan area network) technology is based on the IEEE 802.16 air interface standard suite, which provides the wireless technology for fixed and nomadic data access. WMAN employs orthogonal frequency division multiplexing (OFDM), and supports adaptive modulation and coding depending on the channel conditions. The objective of this paper is to study the performance of the IEEE 802.16d WMAN physical layer under Nakagami model as a Multi-path and frequency-selective fading channel beside the additive white Gaussian noise (AWGN) and Doppler. Finally, we compared it with the Rayleigh fading model. The transmission bit rate, Probability of Error ( ) and estimated SNR have been compared under single/multi path propagation conditions.